Unlocking small-scale fisheries value chains through Information & Communication Technology (ICT) - the case studies of Lamberts Bay & Kleinmond, South Africa - George, Robin Peter (Department of Environmental and Geographical Science, 2020)
Focusing on the small-scale fisheries sector, this thesis examines the question of how the usage of Information and Communication Technology (ICT) can unlock value chain opportunities for fishers. Using a case study approach by focusing on the communities of Lamberts Bay and Kleinmond in the Western Cape of South Africa, it seeks to discover what ICTs should take cognisance of to adequately speak to the value chain realities of small-scale fishers. Some of the work done was observed while engaging with fishers from both communities and other relevant stakeholders during certain engagements with the Abalobi programme, a co-designed smartphone application programme. The emphasis of the research was to speak to different stakeholders who are involved in the value chain and who are engaging with or impact the value chains of small-scale fishing communities. As value chains start with small-scale fishers, their narratives are of utmost importance as they are the initiators of these value chains. The three objectives of this research are to understand the value chain activities of the two communities, differentiate the different value chain activities of the communities at the local, regional and international levels and then contribute to how ICTs such as Abalobi can assist efforts of connecting fishers to their markets. Interviewing and engaging fishers, supportive organisations, authorities, value chain stakeholders in both communities as well as corporates and an ICT specialist, the thesis considers the different perspectives and needs of those involved in the small-scale fisheries value chain. The result of this thesis lead to six ICT requirements being identified to unlocking of small-scale fishing value chains: easy to use, self-sustaining, people-centred and inclusive, integrated, evolving and detailed. Although value chains exist in the sector, ICTs can enable better coordination between stakeholders in it. This research was done to understand how ICTs as a tool can improve and better facilitate the interactions between fishers and their desired markets and that their narratives are brought to the fore in understanding the value chains and in sourcing ICT solutions for them.